2021
DOI: 10.3390/cells11010098
|View full text |Cite
|
Sign up to set email alerts
|

Association between Exosomal miRNAs and Coronary Artery Disease by Next-Generation Sequencing

Abstract: Background: Among various bio-informative molecules transferred by exosomes between cells, micro RNAs (miRNAs), which remain remarkably stable even after freeze-and-thaw cycles, are excellent candidates for potential biomarkers for coronary artery disease (CAD). Methods: Blood samples were collected from the coronary arteries of 214 patients diagnosed with three-vessel CAD and 140 without CAD. After precipitation extraction, the amounts of exosomes were found to decrease with increased age and three-vessel CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…containing circ_0006896 were increased in patients with unstable carotid atherosclerosis (Wen et al, 2021;Zhang et al, 2020). In contrast, and lncRNA SOCS2-AS1 from the circulating EVs were found to be decreased (Chang et al, 2021;de Gonzalo-Calvo et al, 2016;Liang et al, 2020). This demonstrates the great potential of circulating EV-carried ncRNAs as biomarkers in atherosclerotic CVD.…”
Section: Figure 1 Biogenesis and Characterization Of The Different Ex...mentioning
confidence: 88%
See 2 more Smart Citations
“…containing circ_0006896 were increased in patients with unstable carotid atherosclerosis (Wen et al, 2021;Zhang et al, 2020). In contrast, and lncRNA SOCS2-AS1 from the circulating EVs were found to be decreased (Chang et al, 2021;de Gonzalo-Calvo et al, 2016;Liang et al, 2020). This demonstrates the great potential of circulating EV-carried ncRNAs as biomarkers in atherosclerotic CVD.…”
Section: Figure 1 Biogenesis and Characterization Of The Different Ex...mentioning
confidence: 88%
“…The expression levels of several ncRNAs have been found to be increased in circulating EVs from patients with atherosclerosis and coronary artery disease. These include miR‐30e, miR‐92a, miR‐200a, miR‐382, miR‐432, miR‐3613, lncRNA HIF1A‐AS1 and circ_0005540 (Chang et al., 2021; Liu et al., 2019; Wang et al., 2017; Wu et al., 2020; Zhang et al., 2017). Serum‐derived EVs and their miR‐32, miR‐149 and miR‐942 were increased in patients with stable coronary artery disease, while serum‐derived EVs containing circ_0006896 were increased in patients with unstable carotid atherosclerosis (Wen et al., 2021; Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that TGF-β could play a direct role in -3613-3p expression when acquiring a senescent MSC phenotype. Previous studies have directly linked increased expression of exosome -3613-3p to activating invasive cellular and mechanical properties [ 33 , 51 ]. Therefore, reduced expression of 3613-3p with SB505 treatment could indicate that these MSCs possess limited activation potential to acquire CAF-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can integrate their effects to accomplish a nuanced result, no matter whether the result is beneficial or detrimental, by controlling the expression of many targets and gene networks. Chang et al identified eight exosomal miRNA profiles from exosomes extracted from coronary blood samples as potential biomarkers and predictors of stable CA [ 42 ]. Some miRNAs, such as miR-139-5p [ 43 ], miR-145 [ 44 ], miR-100 [ 45 ], miR-194-5p [ 46 ], miR-199a-3p [ 46 ] and miR-199b-3p [ 46 ], which may regulate CA, have been identified.…”
Section: Discussionmentioning
confidence: 99%